Heat transfer enhancement with nanofluids: A review of recent applications and experiments - Ismail I.A.; Yusoff M.Z.; Ismail F.B.; Gunnasegaran P. (International Information and Engineering Technology Association, 2023)
Data mining; Heat transfer coefficients; Heat transfer performance; Thermal conductivity; Experimental research; Heat transfer efficiency; Heat Transfer enhancement; Nanofluids; Recent researches; Theoretical methods; Nanofluidics